Rheological Behaviour of Nickel -Titanium Powder Mixture Feedstock Prepared by Dual Assymetric Centrifuge (DAC) Speed Mixer - Maso’od, Mashitah; Khushaini, Asif; Ahmad, Rohana; ‘Aini Wahab4,, Nor; Hussain Ismail, Muhammad (International Journal of Engineering and Technology, 2018)
Preparation of porous NiTi alloy by Metal Injection Moulding (MIM) requires several important steps, starting from mixing of elemental powders with polymeric binder until the final process of sintering. In this present work, some initial findings on the powder-binder mixture, so called feedstock were investigated.  Theoretical density of Nickel, Titanium and NiTi powders which were determined using pycnometer are 8.97 g/cm3, 4.58 g/cm3 and 6.36 g/cm3 respectively. The composition for Nickel and Titanium powders mixture studied was 56wt% Ni - 44wt% Ti or nearly around 50.9at% Ni – 49.1at% Ti and mixing torque analysis performed using a Brabender Mixer suggested two powder-binder volume fractions of 61%vol and 64%vol. The elemental powders of Nickel and Titanium with particle size of 20 µm and 22 µm were mixed along with water soluble binder system comprised of Polyethelene Glycol/Polymethyl-metacrylate/Stearic Acid (PEG/PMMA/SA) by a Dual-Asymmetric Centrifuge (DAC) speed mixer. The feedstock prepared was evaluated by flow analysis using Capillary Rheometer at four different temperatures; 120ºC, 130ºC, 140ºC and 150ºC and morphological analysis by scanning electron microscopy (SEM). Results showed that DAC technique used in the present work promoted significantly fast processing of MIM feedstock in comparison with conventional method. Besides, the feedstock prepared exhibited good flow behavior, particularly at the temperature of 140ºC, which is supported by SEM morphology that showed uniform powder-binder bonding.